Design of a digital NHit trigger circuit for nuclear and particle physics experiment - Liu Shangming; Cao Ping; Li Chao; Wang Xiaohu (Dianzi Jishu Yingyong, 2023)
In nuclear and particle physics experiments, due to the influence of the experimental background and detector noise, the experiment needs to pick out valid physical events by the trigger selection, and eliminate the background noise. Aiming at the trigger selection requirements based on hit multiplicity (NHit) in the cases of high event rates in physical experiments, this paper designs a high-performance digital trigger circuit. This circuit has 13 high-speed serial communication interfaces, which support optical fiber data transmission and Gigabit network communication; onboard 32 Gbit DDR4 cache and high-end FPGA to support large-capacity high-speed storage and real-time data processing. Based on this circuit, the real-time hardware NHit trigger algorithm could be run, which could realize fast trigger selection and data readout for the front-end data. At the same time, the circuit is easy to expand and could be flexibly used in different physical experiments. After testing and verification, the transmission rate of one single optical fiber interface could reach 8.125 Gb/s, the uplink transmission rate of SiTCP could reach 949.3 Mb/s, and the actual read and write rates of the DDR4 cache could reach 102.6 Gb/s, which meet the data transmission and caching requirements of digital trigger circuit design.